2019
DOI: 10.1556/2062.2019.66.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Hungarian particle reduplication as local doubling

Abstract: This paper provides a morphosyntactic account of particle reduplication in Hungarian, a case of reduplication whose function is to express repetition of events. The most conspicuous property of this process is that it can only apply when the particle is strictly left adjacent to an overt verb. We develop an analysis in terms of a syntactic process that yields a string of doubled particles that do not form a constituent, following the insight of Piñon (1991), and we propose that reduplication targets subwords a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, the unaffixed reduplicated base either does not take place freely or does not occur with a meaning that is part of the affixed reduplicated construction. 41 Sulaiman stated there are 39 total of affixes in Acehnese, consists of 18 prefixs (such as: meu-, peu-, beu-, neu-, teu-, keu, si-, seu-, ku-, lon-, ta-, ka-, ji-, geu-), 4…”
Section: The Reduplication Inmentioning
confidence: 99%
“…However, the unaffixed reduplicated base either does not take place freely or does not occur with a meaning that is part of the affixed reduplicated construction. 41 Sulaiman stated there are 39 total of affixes in Acehnese, consists of 18 prefixs (such as: meu-, peu-, beu-, neu-, teu-, keu, si-, seu-, ku-, lon-, ta-, ka-, ji-, geu-), 4…”
Section: The Reduplication Inmentioning
confidence: 99%
“…Dedicated studies on the existence of verb-stranding ellipsis and ellipsis after igen can be found in . Particle stranding ellipsis was explicitly studied in Lipták (2012); particle stranding ellipsis with participials was mentioned in Lipták and Kenesei (2017); the impossibility of particle stranding with reduplicated particles in Lipták and Saab (2019) and agreement (mis)matches in particle stranding with adpositional particles in Lipták (2018).…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…The stranded particle can be a simple or a phrasal verbal modifier (for the latter see (506) above). There is one systematic exception that particle stranding cannot do: it cannot strand reduplicated verbal modifiers (Piñón 1991, Lipták andSaab 2019). Such verbal modifiers are possible in Hungarian when reduplicated before the verb and indicate iterativity of the action (513A).…”
Section: Sluicing With Non-wh Remnantsmentioning
confidence: 99%
“…As for the syntactic configuration of V-stranding ellipsis in polarity contexts, I follow my earlier work (Lipták 2013) in taking the elided constituent in verb-echos to be a vP, a constituent that is vacated by the movement of the verb to a higher position, namely T 0 in affirmative clauses. Preverbs (aka verbal particles), when present, move from a VP-internal position to Spec,TP, to precede the verb as well (Surányi 2009a;b) and can form a morphosyntactic word with the verb (Surányi 2009b;Lipták & Saab 2019).…”
Section: The Configuration Of V-stranding Ellipsismentioning
confidence: 99%